Ire1 inhibitors attenuate Candida albicans pathogenicity and demonstrate potential for application in antifungal therapy - Wang, Hua; Li, Mengyan; Wang, Qiuyue; Zhao, Huihai; Jiang, Mengyu; Cui, Qi; Lei, Daxin; Jia, Keran; Wang, Fukun (Frontiers in Microbiology, 2025)
IntroductionCandida albicans is a common opportunistic pathogen responsible for both superficial and invasive infections. The unfolded protein response, triggered by endoplasmic reticulum stress, plays a crucial role in its survival and pathogenicity, with the endoplasmic reticulum stress sensor Ire1 serving as a key regulator. Pharmacological inhibition of Ire1 may therefore represent a novel antifungal strategy.MethodsWe conducted molecular docking to identify small-molecule inhibitors targeting the RNase activity of Candida albicans Ire1, followed by in vitro assays assessing pathogenic traits and in vivo validation using a murine intestinal colonization model.ResultsThree candidate inhibitors—MKC8866, STF083010, and 4μ8c—were predicted to interact with Ire1, but only 4μ8c exhibited consistent inhibitory activity. 4μ8c was found to significantly impair key pathogenic traits, including morphological transformation, adhesion, flocculation, and biofilm formation. Additionally, it enhanced the susceptibility of Candida albicans to antifungal drugs and reduced the expression of virulence-related genes. In vivo studies using a murine intestinal colonization model demonstrated that 4μ8c effectively reduced fungal colonization and intestinal tissue damage caused by Candida albicans.DiscussionThese findings demonstrate that pharmacological targeting of the UPR pathway through Ire1 inhibition is feasible. 4μ8c emerges as a promising candidate that diminishes the adaptability and pathogenicity of Candida albicans, offering new insights into antifungal therapeutic development.